Cement grinding aid containing nano silicon dioxide and preparation method of cement grinding aid
By adding nano-silica, sulfur-containing phenol resin and lignin to the cement aid, an efficient cement aid is prepared, which solves the high cost and low grinding efficiency of the existing cement aids. The problem is that a more efficient grinding process and lower energy consumption are achieved.
Patent Information
- Application Number
- CN202411568099.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
AI Technical Summary
The existing cement aids have high cost and low grinding efficiency. The existing technology has a single grinding component, and the grinding efficiency needs to be improved.
A cement aid containing nano-silica is used, and the composition includes 6-10 parts by weight of nano-silica, 5-8 parts by weight of sulfur-containing phenol resin, 7-15 parts by weight of lignin and 25-40 parts by weight of The water is prepared by specific stirring and reaction steps.
It improves the grinding efficiency of cement, reduces particle agglomeration, improves the dispersion and fluidity of materials during grinding, reduces energy consumption, and improves the fineness of cement.
Smart Images

Figure BDA0005119768190000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement, in particular to a cement grinding aid containing nano silicon dioxide and a preparation method thereof. Background Art
[0002] Cement grinding aid can improve the grinding effect of cement, can be adsorbed on the surface of cement particles, play physical and chemical effects, and improve the output per hour while keeping the mill power constant. The cement grinding aid of the prior art is divided into two categories: solid and liquid, but the cost of two kinds of cement grinding aids is higher, and the grinding efficiency is low. Therefore, how to avoid this phenomenon is the key to solving the problem. As patent CN112408849A has announced a kind of cement grinding aid and preparation method thereof, by adding isooctyl phosphate, it plays a grinding aid dispersion effect, improves grinding efficiency, but its grinding aid component is relatively single, and grinding aid efficiency needs to be improved. Summary of the invention
[0003] 1. Technical issues to be solved
[0004] In view of the deficiencies of the prior art, the present invention provides a cement grinding aid containing nano-silicon dioxide and a preparation method thereof, which has good grinding efficiency and reduces particle agglomeration.
[0005] (II) Technical solution
[0006] To achieve the above object, the present invention provides the following technical solution: a cement grinding aid containing nano-silicon dioxide, comprising the following weight components: 6-10 weight parts of nano-silicon dioxide, 5-8 weight parts of sulfur-containing phenolic resin, 7-15 weight parts of lignin, and 25-40 weight parts of water.
[0007] Preferably, the preparation method of the sulfur-containing phenolic resin is:
[0008] (1) adding dimethylaminoethyl methacrylate and 2-bromoethanol to isopropanol solvent, stirring to dissolve, reacting at 75-90° C. for 12-20 hours, and then rotary evaporating and recrystallizing to obtain an olefinic quaternary ammonium salt;
[0009] (2) Add 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine to N,N-dimethylformamide solvent, introduce nitrogen protection, raise the temperature to 60-80°C, 350-400W / m 2 The mixture was irradiated under low temperature and stirred for reaction for 2-4 hours. After the reaction, it was distilled under reduced pressure, washed and dried to obtain intermediate 1.
[0010] (3) adding intermediate 1 and quaternary olefinic ammonium salt to dimethylformamide solvent, stirring and mixing, reacting at 50-70° C. for 25-40 hours, and then rotary distilling, ether precipitation, filtering and drying to obtain intermediate 2;
[0011] (4) Add phenol, intermediate 2, and formaldehyde aqueous solution into a reactor, heat to 60-80° C. and condense under reflux, stir evenly, add oxalic acid catalyst, react for 3-6 hours, add water after reaction, let stand for stratification, filter, wash and dry to obtain sulfur-containing phenolic resin.
[0012] Preferably, the mass ratio of dimethylaminoethyl methacrylate to 2-bromoethanol in (1) is 1:0.8-1.3.
[0013] Preferably, the mass ratio of 4-maleimidophenol, aminoethanethiol and dimethylphenylphosphine in (2) is 1.1-1.3:1:0.01-0.03.
[0014] Preferably, the mass ratio of the intermediate 1 to the olefinic quaternary ammonium salt in (3) is 1:1.2-1.5.
[0015] Preferably, the mass ratio of phenol, intermediate 2, formaldehyde aqueous solution and oxalic acid catalyst in (4) is 2-3.4:1:3.2-4.1:0.01-0.03.
[0016] Preferably, the preparation method of the cement grinding aid containing nano-silicon dioxide is: adding nano-silicon dioxide, sulfur-containing phenolic resin, lignin and water into a stirrer, stirring at 60-85° C. for 15-25 minutes, and then obtaining the cement grinding aid containing nano-silicon dioxide.
[0017] (III) Beneficial technical effects
[0018] The invention provides a cement grinding aid containing nano silicon dioxide by adding nano silicon dioxide, sulfur-containing phenolic resin, lignin and water into a stirrer and stirring the mixture.
[0019] The tertiary amine group in dimethylaminoethyl methacrylate reacts with the bromine group in 2-bromoethanol to generate a quaternary ammonium salt group, and an olefinic group is introduced to obtain an olefinic quaternary ammonium salt. The olefinic group in 4-maleimidophenol and the thiol group in aminoethanethiol are subjected to an addition reaction (increasing the degree of substitution of the quaternary ammonium salt), and phenolic hydroxyl and amine groups are introduced to obtain intermediate 1. The amine group in intermediate 1 and the olefinic group in the olefinic quaternary ammonium salt are subjected to an addition reaction to obtain intermediate 2. Phenol, intermediate 2, and formaldehyde aqueous solution are reacted to obtain a sulfur-containing phenolic resin.
[0020] The adsorption of phenolic resin molecules on the surface of cement particles can reduce the surface energy of the particles, reduce the aggregation and adsorption between particles, thereby improving the dispersion of materials during the grinding process, improving the grinding efficiency of the mill, and reducing energy consumption; the quaternary ammonium salt can form a thin film on the surface of cement particles, reducing the friction and aggregation between particles, thereby improving the dispersion and fluidity of the powder, not only improving the fineness of cement, but also reducing the energy consumption during the grinding process; the adsorption of sulfur elements contained in it on cement particles can reduce the surface energy of particles and produce point or line defects, thereby reducing the strength and hardness of particles, promoting the generation and expansion of cracks, and helping to improve grinding efficiency. DETAILED DESCRIPTION
[0021] Example 1
[0022] (1) adding dimethylaminoethyl methacrylate and 2-bromoethanol to an isopropanol solvent, wherein the mass ratio of dimethylaminoethyl methacrylate to 2-bromoethanol is 1:0.8, stirring to dissolve, reacting at 75° C. for 12 h, and then rotary evaporating and recrystallizing to obtain an olefinic quaternary ammonium salt;
[0023] (2) 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine were added to N,N-dimethylformamide solvent, wherein the mass ratio of 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine was 1.1:1:0.01, nitrogen was introduced for protection, the temperature was raised to 60°C, 350W / m 2 The mixture was irradiated under low temperature and stirred for reaction for 2 h. After the reaction was completed, the mixture was distilled under reduced pressure, washed and dried to obtain intermediate 1.
[0024] (3) adding intermediate 1 and olefinic quaternary ammonium salt to dimethylformamide solvent, wherein the mass ratio of intermediate 1 to olefinic quaternary ammonium salt is 1:1.2, stirring and mixing, reacting at 50° C. for 25 h, and then rotary distilling, ether precipitation, filtering and drying to obtain intermediate 2;
[0025] (4) adding phenol, intermediate 2, and formaldehyde aqueous solution to a reactor, heating to 60° C. and condensing and reflux, stirring evenly, adding oxalic acid catalyst, wherein the mass ratio of phenol, intermediate 2, formaldehyde aqueous solution, and oxalic acid catalyst is 2:1:3.2:0.01, reacting for 3 hours, adding water after the reaction, standing for stratification, filtering, washing and drying to obtain a sulfur-containing phenolic resin;
[0026] (5) 6 parts by weight of nano-silicon dioxide, 5 parts by weight of sulfur-containing phenolic resin, 7 parts by weight of lignin, and 25 parts by weight of water were added into a stirrer and stirred at 60° C. for 15 min. After stirring, a cement grinding aid containing nano-silicon dioxide was obtained.
[0027] Example 2
[0028] (1) adding dimethylaminoethyl methacrylate and 2-bromoethanol to an isopropanol solvent, wherein the mass ratio of dimethylaminoethyl methacrylate to 2-bromoethanol is 1:1.3, stirring to dissolve, reacting at 90° C. for 20 h, and then rotary evaporating and recrystallizing to obtain an olefinic quaternary ammonium salt;
[0029] (2) 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine were added to N,N-dimethylformamide solvent, wherein the mass ratio of 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine was 1.3:1:0.03, nitrogen was introduced for protection, the temperature was raised to 80°C, and the temperature was 400W / m 2 The reaction was stirred for 4 h under auxiliary light, and after the reaction was completed, the reaction was distilled under reduced pressure, washed and dried to obtain intermediate 1;
[0030] (3) adding intermediate 1 and olefinic quaternary ammonium salt to dimethylformamide solvent, wherein the mass ratio of intermediate 1 to olefinic quaternary ammonium salt is 1:1.5, stirring and mixing, reacting at 70° C. for 40 h, and then rotary distilling, ether precipitation, filtering and drying to obtain intermediate 2;
[0031] (4) adding phenol, intermediate 2, and formaldehyde aqueous solution to a reactor, heating to 80° C. and condensing and reflux, stirring evenly, adding oxalic acid catalyst, wherein the mass ratio of phenol, intermediate 2, formaldehyde aqueous solution, and oxalic acid catalyst is 3.4:1:4.1:0.03, reacting for 6 hours, adding water after the reaction, standing for stratification, filtering, washing, and drying to obtain a sulfur-containing phenolic resin;
[0032] (5) 10 parts by weight of nano-silicon dioxide, 8 parts by weight of sulfur-containing phenolic resin, 15 parts by weight of lignin, and 40 parts by weight of water are added into a stirrer and stirred at 85° C. for 25 min. After stirring, a cement grinding aid containing nano-silicon dioxide is obtained.
[0033] Example 3
[0034] (1) adding dimethylaminoethyl methacrylate and 2-bromoethanol to an isopropanol solvent, wherein the mass ratio of dimethylaminoethyl methacrylate to 2-bromoethanol is 1:1.05, stirring to dissolve, reacting at 82° C. for 16 h, and then rotary evaporating and recrystallizing to obtain an olefinic quaternary ammonium salt;
[0035] (2) 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine were added to N,N-dimethylformamide solvent, wherein the mass ratio of 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine was 1.2:1:0.02, nitrogen was introduced for protection, the temperature was raised to 70°C, 375W / m 2 The reaction was stirred for 3 h under auxiliary light, and after the reaction was completed, the intermediate 1 was obtained by distillation under reduced pressure, washing and drying.
[0036] (3) adding intermediate 1 and olefinic quaternary ammonium salt to dimethylformamide solvent, wherein the mass ratio of intermediate 1 to olefinic quaternary ammonium salt is 1:1.35, stirring and mixing, reacting at 60° C. for 32.5 h, and then rotary distilling, ether precipitation, filtering and drying to obtain intermediate 2;
[0037] (4) adding phenol, intermediate 2, and formaldehyde aqueous solution to a reactor, heating to 70° C. and condensing and reflux, stirring evenly, adding oxalic acid catalyst, wherein the mass ratio of phenol, intermediate 2, formaldehyde aqueous solution, and oxalic acid catalyst is 2.7:1:3.65:0.012, reacting for 4.5 hours, adding water after the reaction, standing for stratification, filtering, washing and drying to obtain a sulfur-containing phenolic resin;
[0038] (5) 8 parts by weight of nano-silicon dioxide, 6.5 parts by weight of sulfur-containing phenolic resin, 11 parts by weight of lignin, and 32.5 parts by weight of water were added into a stirrer and stirred at 72° C. for 20 min. After stirring, a cement grinding aid containing nano-silicon dioxide was obtained.
[0039] Example 4
[0040] (1) adding dimethylaminoethyl methacrylate and 2-bromoethanol to an isopropanol solvent, wherein the mass ratio of dimethylaminoethyl methacrylate to 2-bromoethanol is 1:0.8, stirring to dissolve, reacting at 75° C. for 12 h, and then rotary evaporating and recrystallizing to obtain an olefinic quaternary ammonium salt;
[0041] (2) 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine were added to N,N-dimethylformamide solvent, wherein the mass ratio of 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine was 1.1:1:0.01, nitrogen was introduced for protection, the temperature was raised to 60°C, 350W / m 2 The mixture was irradiated under low temperature and stirred for reaction for 2 h. After the reaction was completed, the mixture was distilled under reduced pressure, washed and dried to obtain intermediate 1.
[0042] (3) adding intermediate 1 and olefinic quaternary ammonium salt to dimethylformamide solvent, wherein the mass ratio of intermediate 1 to olefinic quaternary ammonium salt is 1:1.5, stirring and mixing, reacting at 70° C. for 40 h, and then rotary distilling, ether precipitation, filtering and drying to obtain intermediate 2;
[0043] (4) adding phenol, intermediate 2, and formaldehyde aqueous solution to a reactor, heating to 80° C. and condensing and reflux, stirring evenly, adding oxalic acid catalyst, wherein the mass ratio of phenol, intermediate 2, formaldehyde aqueous solution, and oxalic acid catalyst is 3.4:1:4.1:0.03, reacting for 6 hours, adding water after the reaction, standing for stratification, filtering, washing, and drying to obtain a sulfur-containing phenolic resin;
[0044] (4) adding phenol, intermediate 2, and formaldehyde aqueous solution to a reactor, heating to 70° C. and condensing and reflux, stirring evenly, adding oxalic acid catalyst, wherein the mass ratio of phenol, intermediate 2, formaldehyde aqueous solution, and oxalic acid catalyst is 2.7:1:3.65:0.012, reacting for 4.5 hours, adding water after the reaction, standing for stratification, filtering, washing and drying to obtain a sulfur-containing phenolic resin;
[0045] (5) 8 parts by weight of nano-silicon dioxide, 6.5 parts by weight of sulfur-containing phenolic resin, 11 parts by weight of lignin, and 32.5 parts by weight of water were added into a stirrer and stirred at 72° C. for 20 min. After stirring, a cement grinding aid containing nano-silicon dioxide was obtained.
[0046] Example 5
[0047] (1) adding dimethylaminoethyl methacrylate and 2-bromoethanol to an isopropanol solvent, wherein the mass ratio of dimethylaminoethyl methacrylate to 2-bromoethanol is 1:1.3, stirring to dissolve, reacting at 90° C. for 20 h, and then rotary evaporating and recrystallizing to obtain an olefinic quaternary ammonium salt;
[0048] (2) 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine were added to N,N-dimethylformamide solvent, wherein the mass ratio of 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine was 1.3:1:0.03, nitrogen was introduced for protection, the temperature was raised to 80°C, and the temperature was 400W / m 2 The reaction was stirred for 4 h under auxiliary light, and after the reaction was completed, the reaction was distilled under reduced pressure, washed and dried to obtain intermediate 1;
[0049] (3) adding intermediate 1 and olefinic quaternary ammonium salt to dimethylformamide solvent, wherein the mass ratio of intermediate 1 to olefinic quaternary ammonium salt is 1:1.35, stirring and mixing, reacting at 60° C. for 32.5 h, and then rotary distilling, ether precipitation, filtering and drying to obtain intermediate 2;
[0050] (4) adding phenol, intermediate 2, and formaldehyde aqueous solution to a reactor, heating to 70° C. and condensing and reflux, stirring evenly, adding oxalic acid catalyst, wherein the mass ratio of phenol, intermediate 2, formaldehyde aqueous solution, and oxalic acid catalyst is 2.7:1:3.65:0.012, reacting for 4.5 hours, adding water after the reaction, standing for stratification, filtering, washing and drying to obtain a sulfur-containing phenolic resin;
[0051] (5) 6 parts by weight of nano-silicon dioxide, 5 parts by weight of sulfur-containing phenolic resin, 7 parts by weight of lignin, and 25 parts by weight of water were added into a stirrer and stirred at 60° C. for 15 min. After stirring, a cement grinding aid containing nano-silicon dioxide was obtained.
[0052] Example 6
[0053] (1) adding dimethylaminoethyl methacrylate and 2-bromoethanol to an isopropanol solvent, wherein the mass ratio of dimethylaminoethyl methacrylate to 2-bromoethanol is 1:0.8, stirring to dissolve, reacting at 75° C. for 12 h, and then rotary evaporating and recrystallizing to obtain an olefinic quaternary ammonium salt;
[0054] (2) 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine were added to N,N-dimethylformamide solvent, wherein the mass ratio of 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine was 1.1:1:0.01, nitrogen was introduced for protection, the temperature was raised to 60°C, 350W / m 2 The mixture was irradiated under low temperature and stirred for reaction for 2 h. After the reaction was completed, the mixture was distilled under reduced pressure, washed and dried to obtain intermediate 1.
[0055] (3) adding intermediate 1 and olefinic quaternary ammonium salt to dimethylformamide solvent, wherein the mass ratio of intermediate 1 to olefinic quaternary ammonium salt is 1:1.2, stirring and mixing, reacting at 50° C. for 25 h, and then rotary distilling, ether precipitation, filtering and drying to obtain intermediate 2;
[0056] (4) adding phenol, intermediate 2, and formaldehyde aqueous solution to a reactor, heating to 80° C. and condensing and reflux, stirring evenly, adding oxalic acid catalyst, wherein the mass ratio of phenol, intermediate 2, formaldehyde aqueous solution, and oxalic acid catalyst is 3.4:1:4.1:0.03, reacting for 6 hours, adding water after the reaction, standing for stratification, filtering, washing, and drying to obtain a sulfur-containing phenolic resin;
[0057] (5) 10 parts by weight of nano-silicon dioxide, 8 parts by weight of sulfur-containing phenolic resin, 15 parts by weight of lignin, and 40 parts by weight of water are added into a stirrer and stirred at 72° C. for 20 min. After stirring, a cement grinding aid containing nano-silicon dioxide is obtained.
[0058] Comparative Example 1
[0059] 10 parts by weight of nano-silicon dioxide, 15 parts by weight of lignin and 40 parts by weight of water were added into a stirrer and stirred at 72° C. for 20 minutes to obtain a cement grinding aid containing nano-silicon dioxide.
[0060] The cement grinding aids of Examples 1-6 and Comparative Example 1 of the present invention were made into 18 wt % aqueous solutions, and were evenly sprayed on the surface of the cement material to be ground at a dosage of 0.03 wt %. The cement was ground for 15 min and the specific surface area of the cement was tested. The test results are shown in Table 1.
[0061] Table 1: Grinding aids tested.
[0062]
[0063] It can be seen from Table 1 that, compared with Comparative Example 1, the specific surface area of cement particles in Examples 1-6 of the present invention is increased.
[0064] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A cement grinding aid containing nano-silicon dioxide, characterized in that: The invention comprises the following components by weight: 6-10 parts by weight of nano silicon dioxide, 5-8 parts by weight of sulfur-containing phenolic resin, 7-15 parts by weight of lignin and 25-40 parts by weight of water.
2. The cement grinding aid containing nano silicon dioxide according to claim 1, characterized in that, The preparation method of the sulfur-containing phenolic resin is: (1) adding dimethylaminoethyl methacrylate and 2-bromoethanol to isopropanol solvent, stirring to dissolve, reacting at 75-90° C. for 12-20 hours, and then rotary evaporating and recrystallizing to obtain an olefinic quaternary ammonium salt; (2) Add 4-maleimidophenol, aminoethanethiol, and dimethylphenylphosphine to N,N-dimethylformamide solvent, introduce nitrogen protection, raise the temperature to 60-80°C, 350-400W / m 2 The mixture was irradiated under low temperature and stirred for reaction for 2-4 hours. After the reaction, it was distilled under reduced pressure, washed and dried to obtain intermediate 1. (3) adding intermediate 1 and quaternary olefinic ammonium salt to dimethylformamide solvent, stirring and mixing, reacting at 50-70° C. for 25-40 hours, and then rotary distilling, ether precipitation, filtering and drying to obtain intermediate 2; (4) Add phenol, intermediate 2, and formaldehyde aqueous solution into a reactor, heat to 60-80° C. and condense under reflux, stir evenly, add oxalic acid catalyst, react for 3-6 hours, add water after reaction, let stand for stratification, filter, wash and dry to obtain sulfur-containing phenolic resin.
3. The cement grinding aid containing nano silicon dioxide according to claim 2, characterized in that, The mass ratio of dimethylaminoethyl methacrylate to 2-bromoethanol in (1) is 1:0.8-1.
3.
4. The cement grinding aid containing nano silicon dioxide according to claim 2, characterized in that, The mass ratio of 4-maleimidophenol, aminoethanethiol and dimethylphenylphosphine in (2) is 1.1-1.3:1:0.01-0.
03.
5. The cement grinding aid containing nano silicon dioxide according to claim 2, characterized in that, The mass ratio of the intermediate 1 to the olefinic quaternary ammonium salt in (3) is 1:1.2-1.
5.
6. The cement grinding aid containing nano silicon dioxide according to claim 2, characterized in that, The mass ratio of phenol, intermediate 2, formaldehyde aqueous solution and oxalic acid catalyst in (4) is 2-3.4:1:3.2-4.1:0.01-0.
03.
7. A method for preparing a cement grinding aid containing nano-silicon dioxide as claimed in any one of claims 1 to 6, characterized in that: The preparation method of the cement grinding aid containing nano-silicon dioxide is as follows: adding nano-silicon dioxide, sulfur-containing phenolic resin, lignin and water into a stirrer, stirring at 60-85° C. for 15-25 minutes, and then obtaining the cement grinding aid containing nano-silicon dioxide.